2004
DOI: 10.1113/expphysiol.2004.027649
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term structural and functional consequences of cardiac ischaemia–reperfusion injury in vivo in mice

Abstract: The short-term (<24 h) consequences of oxidative stress induced by ischaemia-reperfusion (IR) have been studied extensively in the mouse heart. However, much less is known about the long-term effects inflicted by a brief ischaemic period on the murine heart. We therefore examined the structural and functional consequences of a 30 min ischaemic period after 2 and 8 weeks of reperfusion and compared these to the effects induced by permanent occlusion of the left anterior descending coronary artery (LAD). The lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…This may reflect compensatory ventricular hypertrophy. Myocyte hypertrophy has been described as early as 3 days after infarction in coronary artery ligation models [41] and can be seen within 2-3 weeks after onset of hemodynamic loading in mouse and rat models of myocardial ischemia-reperfusion injury [42,43]. Hypertrophy is a major element of ventricular remodeling after MI, and a frequent precursor of congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect compensatory ventricular hypertrophy. Myocyte hypertrophy has been described as early as 3 days after infarction in coronary artery ligation models [41] and can be seen within 2-3 weeks after onset of hemodynamic loading in mouse and rat models of myocardial ischemia-reperfusion injury [42,43]. Hypertrophy is a major element of ventricular remodeling after MI, and a frequent precursor of congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the enlargement of EDV and the relative thickening of remote regions of LV suggest an eccentric hypertrophic response to I/R injury. De Celle et al (6) studied LV remodeling in mice until 8-wk post-I/R and also reported a positive correlation between infarct size and ventricular weight. This long-term remodeling response can be explained as a compensatory mechanism for reduced cardiac contractility caused by time-dependent functional and structural damage caused by I/R.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the permanent ligation model of MI, which induces rapid thinning of the infarcted LV wall and chamber dilatation, the I/R model of MI leads to slow-developing LV remodeling that is generally complete by 3-6 mo and recapitulates some features of LV remodeling in humans with reperfused MI (3,11,26). The results for echocardiographic analysis at 2 wk in the LacZ (n ϭ 5)-and HO-1 (n ϭ 5)-treated animals are shown in Fig.…”
Section: Aav-mediated Ho-1 Gene Transfer Preserves Echocardiographic mentioning
confidence: 99%